Biologia reprodutiva do camarão sete-barbas Xiphopenaeus kroyeri (Heller, 1862) capturado no litoral Sul do Espírito Santo, Brasil. - Santos, Amanda Soares dos (2023)
Fish have been prominent in the diet due the great demand of consumers who are committed to variety and health improvement through nutrition and food. Regarding the crustacean’s production, the seabob shrimp (Xiphopenaeus kroyeri) can be found in all coastal states and is one of the most captured species in the country. In the state of Espírito Santo, the capture of this fishing resource represents more than 90% of the shrimp fishery, however, studies about the dynamics reproduction with macroscopic and microscopic analyzes to guide an adequate closed season are scarce. The objective of the present study is to characterize the gonadal development stage associating macroscopic and microscopic analyzes of the seabob shrimp Xiphopenaeus kroyeri ovaries captured on the southern coast of Espírito Santo and to present their reproductive dynamics, in order to provide information for the elaboration of recommendations for sustainable fishing of this species of great economic importance for Brazilian fisheries, especially for the state of Espírito Santo, Brazil. To this end, monthly trawls have been performed from March 2019 to February 2020 in Espírito Santo’s coast, at the cities of Anchieta, Piúma and Itapemirim. After sampling, the specimens were added to plastic bags and stored in a cooler with ice for transport. In the laboratory, still fresh, the seabob shrimp’s specie were identified and separated, as to sex, based on the external structure, and the total length (CT), cephalothorax length (CL) and total wet weight (W) were measured. An average of 304 shrimp were randomly sampled macroscopically each month. The females were classified according to the macroscopic maturation stage from the observation of the morphology of the ovaries through the shrimp carapace, as well as the color of the ovaries. For the histological analysis of the females, a monthly subsample of approximately 20 females of the total number of females sampled macroscopically was used. In total, 3.658 specimens of X. kroyeri were collected during the twelve months of sampling. Of this total, 1.831 were females (50,05%) and 1.827 were males (49,95%). There was no significant difference in the sex ratio 1:1 (female:male) of shrimps collected. The females stood out in a greater range of lengths and weight than the male specimens. In the ovaries macroscopic analysis, five maturation stages were found: immature, in initial maturation, in advanced maturation, mature and spawned. The presence of mature females was observed in all collection months. A greater number of mature females appeared in the months of May and July. April was the month that indicated a recruitment season for the species. The rainfall had a significantly correlated with mature females. The mean size at first gonadal maturation (CL50) of females was estimated at 1.7 cm. Based on the results, the current closed season of X. kroyeri does not meet the reproduction and recruitment stages on the south coast of Espírito Santo.